All Days 2006
DOI: 10.2118/100357-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Revolutionary Scale-Control Product for the Control of Near-Well Bore Sulfate Scale within Production Wells by the Treatment of Injection Seawater

Abstract: The formation of sulfate scales arising from the injection of seawater into hydrocarbon-bearing formations for pressure maintenance and secondary oil recovery has been a significant problem in many onshore/offshore operations. To address this, batch scale inhibitor squeeze treatments, scale removal, and modification of the injection brine (sulfate removal, produced water injection, aquifer water injection) have been applied with varying degrees of success. The development of deepwater projects, where conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It can be observed that with the prolongation of displacement time, the axial hydrogen signal intensity of both cores gradually decreases, indicating that the damage to the cores by injected water increases with the prolongation of displacement time. Additionally, another important feature can be observed: at the location of the front of the two cores, the intensity of the hydrogen signal is significantly enhanced in the late stage of flooding, indicating that in the late stage, the uncemented scale particles as well as the weakly cemented clay particles that were washed out by the water were carried by the water flow and transported along the throat to the back of the cores, 41 and the transportation of the solid particles is shown in Figure 7. The water phase occupies the space at the front that has been washed out, resulting in the hydrogen signal at the front is then significantly enhanced.…”
Section: Experimental Study Of Nmr Displacement Inmentioning
confidence: 99%
“…It can be observed that with the prolongation of displacement time, the axial hydrogen signal intensity of both cores gradually decreases, indicating that the damage to the cores by injected water increases with the prolongation of displacement time. Additionally, another important feature can be observed: at the location of the front of the two cores, the intensity of the hydrogen signal is significantly enhanced in the late stage of flooding, indicating that in the late stage, the uncemented scale particles as well as the weakly cemented clay particles that were washed out by the water were carried by the water flow and transported along the throat to the back of the cores, 41 and the transportation of the solid particles is shown in Figure 7. The water phase occupies the space at the front that has been washed out, resulting in the hydrogen signal at the front is then significantly enhanced.…”
Section: Experimental Study Of Nmr Displacement Inmentioning
confidence: 99%
“…British Petroleum (BP) Exploration were the first to report the development of a microemulsion system in oilfield scale inhibition applications. They synthesized microemulsified SIs in order to increase the SI squeeze lifetimes. …”
Section: Nanomaterials For Scale Inhibitionmentioning
confidence: 99%